Infrastructural provision support for economic development in the context of responding to modern challenges - Vasin, Arsenii (Herald of Economics, 2024)
Introduction. The decisive role of infrastructure in ensuring economic development acquires special importance in the context of overcoming crisis phenomena and requires the development of adequate implementation mechanisms. In this connection, the need to substantiate the infrastructural support for the development of Ukraine’s economy, taking into account modern challenges, is actualized, which would make it possible to form a methodological basis for the direction of the infrastructure to solve the tasks of wartime and post-war reconstruction. Purpose of the study. The purpose of the article is a systematic analysis of the processes of forming infrastructural support for the development of the economy, taking into account modern challenges, and, on this basis, substantiating the directions for further development of the infrastructural component of the economic system. Research methods. In the process of research and writing the article, the following methods were used: system analysis, systematization, generalization, comparison, the method of system analysis, logical and dialectical methods. Results. The article substantiates the role of infrastructural support in the formation of the institutional environment of economic development. The essence of the infrastructure is revealed and approaches to its consideration are given, taking into account various criteria. The essence of infrastructural support for the development of the economy in its systemic and process aspects is revealed, and a list of functions, at the implementation of which it is oriented, is given. It was emphasized that infrastructure provision is in the process of transformations caused by modern requirements and challenges, among which the following are highlighted: challenges of wartime and post-war renewal; development trends of the post-industrial society; comprehensive informatization and digitization of economic life, strengthening the role of knowledge resources in the organization of economic activities; the conditions for the entry of the national economy into the globalization space; European integration aspirations of Ukraine; challenges of implementing the principles of sustainable development. It was concluded that building a model of effective infrastructural support for the development of the economy, taking into account the given conditions, is a challenge to the public administration system. Prospects. Building a model of effective infrastructural support for the development of the economy, taking into account modern requirements and conditions with the involvement of the potential of intersectoral interaction, is a challenge to the public administration system and the subject of further research.